Analysis of Helicobacter pylori vacA andcagA genotypes and serum antibody profile in benign and malignant gastroduodenal diseases. Issue 2 (1st August 1998) - Basso, D; Navaglia, F; Brigato, L; Piva, M G; Toma, A; Greco, E; Di Mario, F; Galeotti, F; Roveroni, G; Corsini, A; Plebani, M
Abstract : Background — Helicobacter pylori species comprise different strains, cytotoxic and non-cytotoxic, which can be identified on the basis of their genomic pattern. Aims —(1) To evaluate the polymorphism of the vacA gene and to ascertain whether the cagA gene is present in patients with gastric adenocarcinoma. (2) To study the anti- H pylori antibody profile using western blotting. Patients —Twenty one patients with gastric adenocarcinoma and 71 with H pylori associated benign disease (nine gastric ulcer, 29 duodenal ulcer, 25 antral gastritis, and eight duodenitis). Methods —The polymerase chain reaction was used to verify the presence or absence of cagA and to study the polymorphism of vacA in gastric mucosal samples obtained during endoscopy for patients with benign diseases and at surgery for patients with gastric adenocarcinoma. Fasting sera were used to assess anti- H pylori antibodies against different H pylori antigens by western blotting. Results — cagA gene and the allele s1 of vacA were significantly less frequent in patients with antral gastritis (60% and 60%) compared with patients with gastric adenocarcinoma (94% and 100%) and with other non-malignant gastroduodenal diseases (93% and 87%) (χ 2 =16.01, p<0.001; and χ 2 =13.97, p<0.01). In patients with gastric adenocarcinoma, antibodies against a 74 kDa H pylori antigen were less frequently found than in patients with benign diseases. Conclusions — H pylori infection caused by cagA positive/ vacA s1 strains is a frequent finding in patients with gastric adenocarcinoma. Prospective studies are needed to confirm whether the low incidence of positive serological response to the 74 kDa H pylori antigen in patients with gastric adenocarcinoma is important.